A FALCO Zrt. Puskás Tivadar utcai telephelye zajkibocsátásának és zajterhelésének elemzése lakókörnyezetben - Temesi Tamara (2021)
The aim of my thesis was to investigate a noise-related complaint from a resident at the FALCO Zrt.'s Puskás Tivadar Road site. For this purpose, after a detailed survey of the site, the industrial park and the residential area, I carried out three night-time noise measurements. I then aggregated the results and calculated the impact area as specified in the standard using Microsoft Excel. After determining the plant sound power levels, I examined the noise exposure in front of the complainant's property, which proved that, contrary to the complainant's claim, the exceedance was not caused by FALCO Zrt.